Gender Issues in Ethiopia : Implementing the National Policy on Women - World Bank (Washington, DC, 2012)
The National Policy on Women (Women's Policy) formulated in 1993, aimed to create appropriate structures within government offices and institutions to establish equitable and gender-sensitive public policies. The Government of Ethiopia in 1995, under its new constitution, renewed its commitment towards this policy. The government initiated an ambitious and extensive process of regionalization, whereby new regional boundaries were demarcated and administrative powers devolved to regional governments which were authorized to implement all development policies. This represented a departure from the earlier practice of centralized project management by ministries. This more participatory and decentralized form of governance made the implementation of the national policy a more challenging endeavor. There was correspondingly a great need to build the delivery capacity of the regional governments. While the central level of government promoted gender-sensitive policies and development interventions, very little was known about the constraints and issues at the regional levels.